The AdS 3 × S 1 chiral ring - Sujay K. Ashok (SpringerOpen, 2021)
Abstract We study AdS 3 × S 1 × Y supersymmetric string theory backgrounds with Neveu-Schwarz-Neveu-Schwarz flux that are dual to N $$ \mathcal{N} $$ = 2 superconformal theories on the boundary. We classify all worldsheet vertex operators that correspond to space-time chiral primaries. We compute space-time chiral ring structure constants for operators in the zero spectral flow sector using the operator product expansion in the worldsheet theory. We find that the structure constants take a universal form that depends only on the topological data of the N $$ \mathcal{N} $$ = 2 superconformal theory on Y.